UTILIZING EDUCATIONAL PLATFORMS IN A REGULAR CLASSROOM SETTING - Habibovic, Ervin (Advances in Social Sciences Research Journal, 2018)
New technological era is changing the education world of today. It provides different ways for teaching on a daily basis. Old methods are still applicable and they produce results but they are not enough to satisfy the needs of current generation. Students are tech-savvy these days, online bound, they are young individuals who see and experience world in a new way, through different lens. They are being educated daily through the usage of technology. The virtual world is shaping the way students think, learn and grow. We need to realize that youngsters cannot be pulled back from keeping up with their own time. The educational system needs to advance and adapt fast. Considering that virtual reality is the current global trend, one solution is to create virtual classroom or a platform where students could learn online together with their teachers. Tests can be done online, competitions are being organized on the phone which students are using daily, materials are exchanged on the go, students, teachers and parents can seamlessly exchange information. All of this is easily accessible on any device. These are only some of the benefits a virtual classroom setting can bring in educational sector of today. It all starts with one teacher that will open up their mindset to creating a new interactive atmosphere for their students and teachers alike. Keywords: education, online, platform, classroom, student